(untitled) (Universa Medicina, 2019)
Background Traumatic brain injury (TBI) is among the leading causes of mortality and long-term disability. Prognosis assessment is a primary factor of clinical decision-making by emergency physicians. This study aimed to investigate the prognostic factors of TBI in the patients admitted to a typical emergency department. Methods This prospective cohort study was conducted involving 100 TBI patients. Baseline characteristics, including age, gender, Glasgow Coma Scale (GCS), and vital signs were recorded. Blood tests and brain CT scans were collected. The patients were followed-up three months after the date of admission. The observed outcomes were categorized as recovery without complication, recovery with complication, or death. Statistical analysis was performed using the simple and multivariate binary logistic regression in the software IBM SPSS version 19. Results The most common brain CT scan findings were subarachnoid hemorrhage (21.0%) and epidural hemorrhage (20.0%). In the follow-up performed three months after the admission, 47 patients (47.0%) had died, 39 (39.0%) were suffering from complications, and 14 patients (14.0%) were recovering without complications. Simple binary logistic regression showed that older age (OR=3.28, 95% C.I.=1.27-8.41), minor/moderate head trauma (OR=13.93, 95% C.I.=1.73-112.11), severe head trauma (OR=54.40, 95% C.I.=5.71-517.56) and presence of deep skull fracture (OR=8.92, 95% C.I.=1.04-75.53) were statistically significant predictors of mortality. Multivariate logistic regression showed that mortality chance was higher in elderly (OR=7.45, 95% C.I.=2.02-27.36), minor/moderate head trauma (OR=26.87, 95% C.I.=2.42-298.25) and severe head trauma (OR=127.97, 95% C.I.=9.11-1796.28). Conclusion This study demonstrated that severe head trauma was the most predicted risk factor of poorer clinical outcomes after TBI.